COVID-19 - The clinical consequences of social isolation and the relation with sleep bruxism and comorbidities - Cunha, Thays Crosara Abrahão; Cunha, Thulio Marquez; Matoso, Abadia Gilda Buso; Januzzi, Eduardo; Dal-Fabbro, Cibele (Sleep Science, 2021)
SARS-COV-2 is a highly pathogenic coronavirus that causes the disease known as COVID-19, which has infected more than 100 million people worldwide. The main form of containment of the pandemic is social isolation. However the isolation, the severity of the COVID-19 disease, the uncertainty of the future and the economic impact are the possible causes of anxiety as an adverse effect of the pandemic. The literature describes the possible association between anxiety with poor sleep quality, exacerbation of painful conditions, gastroesophageal reflux disease, increased consumption of drugs and the possibility of developing or enhancing sleep bruxism. Health professionals should keep in mind the possibility of overlapping with the different clinical conditions mentioned and the need for a multi-professional team to manage these patients.
Keywords: Gastroesophageal reflux; Pandemic; Sleep bruxism; Anxiety obesity